Night Soil: Origins, Discontinuities, and Opportunities for Bridging the Metabolic Rift - Nicholas C. Kawa; Yang Ding; Jo Kingsbury; Kori Goldberg; Forbes Lipschitz; Mitchell Scherer; Fatuma Bonkiye (Ethnobiology Letters, 2019)
For millennia, people have relied on human excrement or “night soil” as a source of agricultural fertilization. Following industrialization, however, the use of this resource became considerably limited. In this article, we provide a brief overview of the historical use of human excreta for agricultural application at varying scales of management, from early Amazonian farming middens to regional networks of night soil trade in imperial China. We then draw attention to the factors that led to the discontinuation of night soil usage during industrialization, placing focus on the “culture of flushing” that developed along with the adoption of the hydraulic sanitation system. To conclude, we consider how improved management of human excreta in the contemporary world can have important consequences for agricultural production, despite the ongoing challenges posed by what Marxian scholars refer to as the metabolic rift—the disruption of the earth’s socio-ecological cycles brought on by industrial capitalism.